Assessing spatial accessibility of community pharmacies in England and Wales using floating catchment area techniques - Stephen D. Clark; Andy Newing (Journal of Pharmaceutical Policy and Practice)
Background Community pharmacies in England and Wales are taking on a broader range of primary care responsibilities in order to ease pressure on other health services. ‘Pharmacy First’, launched in 2024, allows patients to access treatment for a range of common conditions directly from a pharmacy without the need to consult a GP. However, funding and workforce pressures have resulted in a number of pharmacy closures in recent years. This study assesses the geographical accessibility of community pharmacies in England and Wales and identifies the impact of these recent closures.Methods Using open data on pharmacy locations and opening hours this study calculates a Spatial Accessibility Index (SPAI) for access to pharmacies by car in 2022 and 2024. We use a Modified Huff Variable Three Step Floating Catchment Area (MHV3SFCA), a variant of the Floating Catchment Area (FCA) technique.Results Suburban and rural neighbourhoods tend to have poorer access to community pharmacies, whilst more deprived neighbourhoods generally have comparatively better access. We identify neighbourhoods which could be classed as ‘pharmacy deserts’, which are primarily located in rural areas. We identify that all neighbourhood area types witness a reduction in overall accessibility to community pharmacies between 2022 and 2024. In total these result in a 10% reduction in the SPAI.Conclusion The MHV3SFCA applied here is novel in its application to community pharmacy accessibility in a UK context. We demonstrate its utility as a tool to identify the impact of changes to the community pharmacy network on accessibility as experienced by different neighbourhoods. We find evidence of a ‘positive pharmacy care law’ and also the existence of some ‘pharmacy deserts’.